PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN TGT PADA SISWA KELAS VIII A SMP NEGERI 1 GIRITONTRO TAHUN PELAJARAN 2022/2023 - Hartanto, Budi (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
This classroom action research aims to increase motivation and learning outcomes through the application of the Teams Games Tournament (TGT) model in science learning material Motion of Objects for class VIII A students of SMP Negeri 1 Giritontro, Academic Year 2022/2023. The object of his research is the motivation and learning outcomes of students in the science subject matter of Object Movement. The types of data collected in this research are primary data and secondary data. Primary data sources are teachers and students, including summative test scores, and observations during the learning process. While secondary data comes from colleagues who become observers. The results of this study indicate an increase in student learning outcomes, this can be seen from the percentage of learning completeness in pre-cycle 46%, in cycle 1 it becomes 73%, and it becomes 92% in cycle 2. Student motivation in pre-cycle learning is low, in cycle 1 being moderate, and in cycle 2 the high category. With the application of the TGT learning model, teachers can change the paradigm from teacher-centered learning to student-centered learning.